«Help» methodology for improving coordination training effectiveness in acrobatics sports - Mischenko, N.; Kolokoltsev, M.; Romanova, E.; Vorozheikin, A.; Bolotin, A.; Vyazovichenko, Y.; Timchenko, N. (Journal of Physical Education and Sport, 2021)
The analysis of modern scientific literature indicates insufficient knowledge of the variable component use in the sports training program for acrobat girls aged 11-12 for their coordination abilities and vestibular stability development. Research aim is to evaluate the effectiveness of «Help» methodology proposed by us for female athletes', aged 11-12, engaged in sports acrobatics at the stage of sports specialization, coordination abilities development. Materials and methods. The participants of the research project were two groups of girls (n=20), aged 11-12, who were engaged in sports acrobatics. The main training sessions in the control (CG) and experimental group (EG) were conducted according to the Russian standard «Sports Acrobatics» (2014). In the annual training macrocycle of the experimental group, the method of performing exercises was expanded. A special set of sports equipment was selected: a balancing disc and a «Bosu» hemisphere, an agility ladder, a trampoline and a skateboard. All exercises on sports equipment were performed in the first half of the main part of the lesson. The skateboard and the «Bosu» hemisphere were additionally used in active games. We called the developed method of coordination training «Help», which is based on the principle of complicating the conditions for performing exercises. In both groups, stage-by-stage testing of the athletes' overall physical, coordination and technical fitness and vestibular stability was carried out. Results. After the research project completion, the athletes of the ?G and EG had an improvement in the indicators values in all tests. The EG athletes, engaged in the «Help» method had more growth values in all tests than the CG athletes. The greatest increase was found in EG girls in tests characterizing general flexibility and speed endurance. At the end of the pedagogical experiment, a significant improvement in the tests of dynamic coordination and vestibular stability was also found in girls of both groups. The greatest increase in the indicators values of coordination tests was shown by EG athletes, engaged in «Help» experimental method. Training according to the experimental method significantly improved the indicators values in the tests of the EG athletes' technical readiness, compared with the CG. Conclusions. The results of testing «Help» method in sports acrobatics classes showed an increase in coordination qualities, vestibular stability, general and technical readiness in girls aged 11-12. The emergence of new complex coordination sports and their inclusion in major international competitions requires the sports community and scientists to search for new pedagogical technologies and techniques for training athletes.